2023
DOI: 10.1111/inr.12829
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' competence levels in disaster nursing management in Turkey: A comparative cross‐sectional study

Abstract: AimThis study aimed to determine nurses’ views of their competence in disaster nursing management.BackgroundIt is an important responsibility of nurses to have the necessary knowledge and skills for the management of disasters and to be prepared for disasters. For this responsibility to be effectively demonstrated, it is important to determine the disaster management competencies of the nurses.MethodsA descriptive, cross‐sectional, and comparative research design was used in this study. The study population co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Despite this, not every nurse is adequately prepared to confront these situations. Studies have confirmed that nurses’ knowledge, skills, and abilities in disaster emergency response are insufficient to deal with such circumstances [ 8 9 ]. Furthermore, it should be noted that the concepts of knowledge, skill, ability, and literacy are distinct and cannot be equated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, not every nurse is adequately prepared to confront these situations. Studies have confirmed that nurses’ knowledge, skills, and abilities in disaster emergency response are insufficient to deal with such circumstances [ 8 9 ]. Furthermore, it should be noted that the concepts of knowledge, skill, ability, and literacy are distinct and cannot be equated.…”
Section: Introductionmentioning
confidence: 99%